An Examination of Methods to Estimate Poverty Line in Indonesia - Muhammad Nashihin (Universitas Islam Indonesia, 2009)
The first objective of this paper is to set out a new approach for estimating regional poverty lines inIndonesia. The approach is referred as a utility-consistent poverty line (UCPL) approach. It is basedon a theory of price index or cost of living index (COLI). The second objective is to examine thedevelopment of methods for estimating poverty lines in general and methods used to estimate regionalpoverty lines in Indonesia. The survey focuses on comparing these methods with UCPL approach.The paper finds out that the existing methods used to estimate poverty line in Indonesia arenot able to generate utility-consistent poverty lines.Keywords: Poverty line, spatial cost of living, food energy intake, ravallion method